PENGARUH AUDIT TENURE, AUDIT FEE, UKURAN KANTOR AKUNTAN PUBLIK DAN AUDIT DELAY TERHADAP KUALITAS AUDIT - Zulfikar Fadillah (2022)
This study aims to determine the effect of audit tenure, audit fee, audit firm size, and audit delay on Audit Quality. The population on this research is financial company who listing in Indonesia Stock Exchange on period 2018 - 2020. This study used purposive sampling technique and obtained 59 company with 179 data. This research is using quantitative research. The research data are analysed using logistic regression analysis with significance level 0,05 (5%). The results showed that Audit Tenure and Audit Delay has no effect on audit quality. Meanwhile Audit Fee had a significant positive on audit quality and Audit firm size had a significant negative on audit quality.